Development of microsatellite markers from loquat, Eriobotrya japonica (Thunb.) Lindl. - Gisbert, Ana D.; Lopez-Capuz, I.; Soriano, J. M.; Llácer, Gerardo; Romero, Carlos; Badenes, María L. (2017)
Loquat (Eriobotrya japonica) is a minor fruit which has become an interesting alternative into the European fruit industry. This interest resulted in a loquat germplasm collection established at the Instituto Valenciano de Investigaciones Agrarias, Valencia, Spain. Currently, it is the main reservoir of this species outside Asia. We developed and characterized the first 21 polymorphic microsatellite loci from a CT/AG-enriched loquat genomic library. The observed heterozygosity ranged between 0.20 and 1.00, expected heterozygosity ranged between 0.17 and 0.81, three markers were multilocus and eight loci departed significantly from Hardy-Weinberg equilibrium. These markers will facilitate diversity and genetic studies into the species.